CRISPR/Cas9 Technology: A Novel Approach to Obesity Research - Khademi, Zahra; Mahmoudi, Zahra; Sukhorukov, Vasily N.; Jamialahmadi, Tannaz; Sahebkar, Amirhossein (Current Pharmaceutical Design, 2024)
Gene editing technology, particularly Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)/CRISPR-associated protein 9 (Cas9) has transformed medical research. As a newly developed genome editing technique, CRISPR technology has strongly assisted scientists in enriching their comprehension of the roles of individual genes and their influences on a vast spectrum of human malignancies. Despite considerable progress in elucidating obesity's molecular pathways, current anti-obesity medications fall short in effectiveness. A thorough understanding of the genetic foundations underlying various neurobiological pathways related to obesity, as well as the neuro-molecular mechanisms involved, is crucial for developing effective obesity treatments. Utilizing CRISPR-based technologies enables precise determination of the roles of genes that encode transcription factors or enzymes involved in processes, such as lipogenesis, lipolysis, glucose metabolism, and lipid storage within adipose tissue. This innovative approach allows for the targeted suppression or activation of genes regulating obesity, potentially leading to effective weight management strategies. In this review, we have provided a detailed overview of obesity's molecular genetics, the fundamentals of CRISPR/Cas9 technology, and how this technology contributes to the discovery and therapeutic targeting of new genes associated with obesity.
Keywords: CRISPR/Cas9